Heterostructure gel electrolyte and preparation method and application thereof
By preparing heterostructured gel electrolytes, the problems of uneven infiltration, monomer residues and large amount of electrolytes in the battery are solved, good wetting and cycling performance are achieved, and the amount of electrolyte is used is reduced.
Patent Information
- Application Number
- CN202411478495.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-28
AI Technical Summary
The existing gel electrolytes have problems such as uneven wetting, monomer residues and large amounts of electrolytes in batteries.
Using a heterostructure gel electrolyte, the monomers A, B, and C are mixed with the initiator and the emulsifier in the presence of water and a chain transfer agent to react in contact to obtain a pre-emulsion. Then, in the presence of the initiator and the emulsifier, the pre-emulsion is added dropwise to the mixture of the buffer and another pre-emulsion for emulsification reaction, and a heterostructure gel electrolyte with structural units A, B, and C are prepared.
It effectively avoids monomer residues, improves wetting properties, reduces the use of electrolytes, improves the circulation performance of the battery, and achieves close bonding with the positive and negative electrodes.
Smart Images

Figure CN119542519A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery material preparation, and in particular to a heterogeneous structure gel electrolyte and a preparation method and application thereof. Background Art
[0002] Liquid electrolyte is one of the important main materials of traditional liquid lithium-ion batteries, but it often has the risk of high usage and easy leakage, which may cause safety hazards. At present, gel polymer electrolyte is considered to be one of the effective means to solve this problem, that is, liquid electrolyte plasticizer is introduced into the organic matrix, which presents a state between solid and liquid. While ensuring ionic conductivity, liquid additives are wrapped inside, presenting a condensed state, which effectively avoids the leakage problem of liquid electrolyte.
[0003] At present, there are mainly the following applications of gel polymer electrolytes in batteries. The first is to dissolve polymer monomers in liquid electrolytes outside the battery and then initiate the preparation of electrolyte membranes. This process has high requirements for the environment, and the internal electrolyte cannot completely penetrate into the pores of the electrode material; the second is to inject a liquid electrolyte precursor containing small molecule monomers, initiators, and cross-linking agents into the battery, and initiate its polymerization into a gel state in situ inside the battery, but a small amount of monomers and initiators will remain inside the battery, affecting the ionic conductivity of the electrolyte, causing side reactions in the battery, and the overall uniformity and wettability of the battery cell are not ideal; the third is to prepare a gel precursor coated diaphragm. This composite diaphragm can be activated into a gel electrolyte after being infiltrated with the electrolyte. This method has a simple process and the battery cell can be uniformly infiltrated as a whole. However, the preparation process of this precursor usually uses a large amount of organic reagents, which is not environmentally friendly. In addition, the above three methods have not completely reduced or even increased the amount of liquid electrolyte used, nor have they improved the energy density of the battery cell.
[0004] CN 117747932A discloses a quasi-solid electrolyte solidified in situ, wherein the raw materials used in the electrolyte contain at least one fluorocarboxylate polymer monomer containing unsaturated polymerizable groups and a fluorocarboxylate polymer monomer containing unsaturated polymerizable groups. The quasi-solid battery made by the technical solution can increase its operating voltage to above 4.2V, and the battery's rate performance, battery cycle performance and safety are all improved, and the disadvantage that the polymer in the traditional solid electrolyte cannot be simultaneously resistant to oxidation and reduction can be improved. However, the injection coefficient of the electrolyte is not reduced, and there will be serious monomer residues after solidification, causing the interface side reaction to deteriorate the battery performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of uneven infiltration of gel electrolyte in the battery, residual monomers and excessive electrolyte in the prior art.
[0006] In order to achieve the above object, the first aspect of the present invention provides a heterogeneous structure gel electrolyte, which contains a structural unit A, a structural unit B and a structural unit C, wherein the molar ratio of the structural unit A, the structural unit B and the structural unit C is 1:0.1-0.4:0.05-0.2;
[0007] The structural unit A is shown in formula (1), the structural unit B is shown in formula (2), and the structural unit C is shown in formula (3);
[0008]
[0009] Wherein, in formula (1) and formula (3), R1 and R3 are each independently selected from C 1-4 Alkoxy, containing at least one oxygen atom as a ring atom C 2-6 Heterocycloalkoxy, phenyl, C 1-4 Alkanoyl, nitro, methylsulfonyl, C 1-4 The sulfonic acid group and C 1-4 One of the alkyl groups;
[0010] In formula (2), R2 is selected from H, -OH, -Li, C 1-4 Alkoxy, containing at least one oxygen atom as a ring atom C 2-6 Heterocycloalkoxy, phenyl and C 1-4 One of the alkyl groups.
[0011] A second aspect of the present invention provides a method for preparing a heterogeneous structure gel electrolyte, the method comprising:
[0012] (1) in the presence of water and a chain transfer agent, monomer A', monomer B', monomer C', initiator I and emulsifier I are mixed to carry out a contact reaction to obtain a pre-emulsion;
[0013] (2) in the presence of initiator ⅠⅠ and emulsifier ⅠⅠ, adding pre-emulsion I to a mixed solution containing a buffer and pre-emulsion II to perform an emulsification reaction to obtain the heterogeneous structure gel electrolyte; the pre-emulsion I and the pre-emulsion II are both the pre-emulsions prepared in step (1), and the weight ratio of the pre-emulsion I to the pre-emulsion II is 1:0.05-0.25;
[0014] Wherein, in step (1), the molar ratio of the monomer A', the monomer B' and the monomer C' is 1:0.1-0.4:0.05-0.2;
[0015] The monomer A' is selected from at least one of the monomers represented by formula (I), the monomer B' is selected from at least one of the monomers represented by formula (II), and the monomer C' is selected from at least one of the monomers represented by formula (III);
[0016] The monomer A', the monomer B', and the monomer C' respectively make the gel electrolyte contain a structural unit A, a structural unit B, and a structural unit C, wherein the structural unit A is as shown in formula (1), the structural unit B is as shown in formula (2), and the structural unit C is as shown in formula (3).
[0017]
[0018]
[0019] The definitions of R1, R2 and R3 are the same as those of R1, R2 and R3 in the first aspect.
[0020] The third aspect of the present invention provides a heterogeneous structure gel electrolyte prepared by the method described in the second aspect.
[0021] The fourth aspect of the present invention provides use of the heterogeneous structure gel electrolyte described in the first aspect or the third aspect in a lithium ion battery.
[0022] Through the above technical solution, the present invention has at least the following advantages:
[0023] The method for preparing heterogeneous structure gel electrolyte provided by the present invention is not affected by monomer residue after polymerization inside the battery cell because the gel precursor is prepared in advance; monomer residue inside the battery is effectively avoided, and wettability is improved; the preparation process is simple, and the finished product can be directly used for diaphragm coating slurry.
[0024] The heterogeneous structure gel electrolyte provided by the present invention effectively solves the problem of uneven wetting of the battery core; since it has a heterogeneous structure with hydrophilic interior and hydrophobic exterior, the hydrophobic base on the exterior of the gel absorbs the electrolyte to swell, while the interior does not absorb the electrolyte, thereby reducing the amount of electrolyte used to achieve cost reduction, while the outer layer of gel drives the electrolyte to achieve better electrode wetting effect, and the gel electrolyte can achieve tight bonding with the positive and negative electrodes.
[0025] In addition, the heterogeneous structure gel electrolyte provided by the present invention has good battery cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the internal structure of the heterogeneous structure gel electrolyte obtained in Example 1 of the present invention and the lithium ion battery prepared therefrom. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] In the present invention, the normal temperature refers to a temperature of 25±2°C.
[0029] In the present invention, “C 1-4 The term "alkyl" refers to a straight chain, branched chain, or cycloalkyl group having 1 to 4 carbon atoms, for example, a straight chain alkyl group having 1, 2, 3, or 4 carbon atoms, a branched chain alkyl group having 3 or 4 carbon atoms, or a cycloalkyl group, including but not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, and the like.
[0030] In the present invention, “C 1-4 The term "alkoxy" refers to a compound consisting of a straight chain or branched chain alkyl group having 1 to 4 carbon atoms and an oxygen atom, including but not limited to methoxy, ethoxy, propoxy, butoxy, etc.
[0031] “C 2-6 The term "epoxy group" refers to a compound containing at least one oxygen atom and at least 2 carbon atoms as ring atoms, with a total of 2, 3, 4, 5 and 6 carbon atoms.
[0032] “C 1-4 The term "alkanoyl" refers to a compound consisting of an acyl group and a straight-chain or branched-chain alkyl group having 1 to 4 carbon atoms in total connected to the acyl group.
[0033] “C 1-4 The term "sulfonic acid group" refers to a compound consisting of a sulfonic acid group and a straight-chain alkyl group or a branched-chain alkyl group having 1 to 4 carbon atoms in total connected to the sulfonic acid group.
[0034] It should be noted that the descriptions of “Ⅰ”, “ⅠⅠ”, etc. involved in the present invention are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the order of the indicated technical features.
[0035] As mentioned above, the first aspect of the present invention provides a heterogeneous structure gel electrolyte, which contains a structural unit A, a structural unit B and a structural unit C, wherein the molar ratio of the structural unit A, the structural unit B and the structural unit C is 1:0.1-0.4:0.05-0.2;
[0036] The structural unit A is shown in formula (1), the structural unit B is shown in formula (2), and the structural unit C is shown in formula (3);
[0037]
[0038] Wherein, in formula (1) and formula (3), R1 and R3 are each independently selected from C 1-4 Alkoxy, containing at least one oxygen atom as a ring atom C 2-6 Heterocycloalkoxy, phenyl, C 1-4 Alkanoyl, nitro, methylsulfonyl, C 1-4 The sulfonic acid group and C 1-4 One of the alkyl groups;
[0039] In formula (2), R2 is selected from H, -OH, -Li, C 1-4 Alkoxy, containing at least one oxygen atom as a ring atom C 2-6 Heterocycloalkoxy, phenyl and C 1-4 One of the alkyl groups.
[0040] Preferably, in formula (1) and formula (3), R1 and R3 are each independently selected from methoxy, C 2-6 Epoxy, phenyl, formyl, acetyl, nitro, methylsulfonyl, C 1-4 One of a sulfonic acid group, a methyl group and an n-butyl group;
[0041] In formula (2), R2 is selected from H, -OH, -Li, methoxy, C 2-6 The epoxy group and C 1-4 One of the alkyl groups.
[0042] As mentioned above, the second aspect of the present invention provides a method for preparing a heterogeneous structure gel electrolyte, the method comprising:
[0043] (1) in the presence of water and a chain transfer agent, monomer A', monomer B', monomer C', initiator I and emulsifier I are mixed to carry out a contact reaction to obtain a pre-emulsion;
[0044] (2) in the presence of initiator ⅠⅠ and emulsifier ⅠⅠ, adding pre-emulsion I to a mixed solution containing a buffer and pre-emulsion II to perform an emulsification reaction to obtain the heterogeneous structure gel electrolyte; the pre-emulsion I and the pre-emulsion II are both the pre-emulsions prepared in step (1), and the weight ratio of the pre-emulsion I to the pre-emulsion II is 1:0.05-0.25;
[0045] Wherein, in step (1), the molar ratio of the monomer A', the monomer B' and the monomer C' is 1:0.1-0.4:0.05-0.2;
[0046] The monomer A' is selected from at least one of the monomers represented by formula (I), the monomer B' is selected from at least one of the monomers represented by formula (II), and the monomer C' is selected from at least one of the monomers represented by formula (III);
[0047] The monomer A', the monomer B', and the monomer C' respectively make the gel electrolyte contain a structural unit A, a structural unit B, and a structural unit C, wherein the structural unit A is as shown in formula (1), the structural unit B is as shown in formula (2), and the structural unit C is as shown in formula (3).
[0048]
[0049] The definitions of R1, R2 and R3 are the same as those of R1, R2 and R3 in the first aspect.
[0050] Preferably, in step (1), relative to 100 parts by weight of the monomer combination, the amount of the initiator I is 0.1-0.3 parts by weight, and the amount of the emulsifier I is 0.5-0.8 parts by weight; the monomer combination is the total weight of the monomer A', the monomer B' and the monomer C'.
[0051] Preferably, in step (1), the molar ratio of the monomer A', the monomer B' and the monomer C' is 1:0.1-0.2:0.05-0.08.
[0052] Preferably, the weight ratio of the initiator I to the initiator II is 0.2-0.4:1.
[0053] Preferably, the weight ratio of the emulsifier I to the emulsifier II is 0.4-0.6:1.
[0054] Preferably, in step (1), the amount of the chain transfer agent is 0.1-1 part by weight relative to 100 parts by weight of the monomer combination; the monomer combination is the total weight of the monomer A', the monomer B' and the monomer C'.
[0055] Preferably, the chain transfer agent is selected from at least one of aliphatic mercaptan, sodium dodecyl ether sulfate, sodium dodecyl polyoxyethylene ether sulfate, sodium dodecyl sulfate, 2,4-diphenyl-4-methyl-1-pentene and 2,4-diphenyl-4-ethyl-2-butene, more preferably at least one of sodium dodecyl polyoxyethylene ether sulfate, sodium dodecyl sulfate, 2,4-diphenyl-4-methyl-1-pentene, and further preferably 2,4-diphenyl-4-methyl-1-pentene.
[0056] Preferably, the contact reaction conditions include: a rotation speed of 1200-1400 rpm and a time of 10-20 min.
[0057] Preferably, the temperature of the contact reaction is room temperature.
[0058] Preferably, in step (2), the addition flow rate of the pre-emulsion I is 8-9 mL / min relative to 1 L of the mixed solution.
[0059] Preferably, in the mixed solution, the concentration of the buffer is 4-6 mg / mL.
[0060] Preferably, step (2) further comprises: subjecting the product obtained from the emulsification reaction to a heat preservation treatment for 1-3 hours.
[0061] Preferably, the emulsification reaction conditions include: a rotation speed of 1000-1300 rpm, a time of 200-300 min, and a temperature of 70-90°C.
[0062] Preferably, the initiator I and the initiator II are each independently selected from at least one of azobisisobutyronitrile, dibenzoyl peroxide, ammonium persulfate, sodium persulfate and potassium persulfate, more preferably at least one of ammonium persulfate, sodium persulfate and potassium persulfate, further preferably ammonium persulfate.
[0063] Preferably, the emulsifier I and the emulsifier II are each independently selected from anionic emulsifiers and / or nonionic emulsifiers.
[0064] Further preferably, the anionic emulsifier is selected from at least one of sodium lauryl ether sulfate, sodium lauryl polyoxyethylene ether sulfate, sodium lauryl sulfate, potassium lauryl sulfate, sodium dodecyl sulfonate, potassium dodecyl sulfonate and ammonium dodecyl sulfonate, more preferably at least one of sodium lauryl sulfate, potassium dodecyl sulfate and sodium dodecyl sulfonate.
[0065] Further preferably, the nonionic emulsifier is at least one selected from polyoxyethylene alkyl ether, alkylphenol polyoxyethylene ether, sorbitol and polysorbate.
[0066] As mentioned above, the third aspect of the present invention provides a heterogeneous structure gel electrolyte prepared by the method described in the second aspect.
[0067] Preferably, the inner core of the heterogeneous structure gel electrolyte is a hydrophilic group, and the outer core is a hydrophobic group.
[0068] As mentioned above, the fourth aspect of the present invention provides the use of the heterogeneous structure gel electrolyte described in the first aspect or the third aspect in a lithium ion battery.
[0069] Preferably, the application method comprises: coating the heterogeneous structure gel electrolyte on a battery separator, and then preparing the lithium-ion battery through the processes of lamination and liquid injection.
[0070] The present invention has no particular limitation on the coating method, which may be spray coating, roller coating, etc., as long as uniform coating can be achieved.
[0071] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the compounds and reagents used are all commercially available, wherein the reagents are all purchased from Aladdin Company.
[0072] Monomer A'-1: methyl methacrylate, CAS number 80-62-6, structural formula
[0073] Monomer A'-2: n-butyl methacrylate, CAS No. 97-88-1, structural formula
[0074]
[0075] Monomer A'-3: Glycidyl methacrylate, CAS No. 106-91-2, structural formula
[0076]
[0077] Monomer B'-1: Lithium acrylate, CAS No. 13270-28-5, structural formula
[0078] Monomer B'-2: acrylic acid, CAS No. 79-10-7.
[0079] Monomer B'-3: phenyl acrylate, CAS number 937-41-7.
[0080] Monomer C'-1: glycidyl acrylate, CAS number 106-90-1.
[0081] Monomer C'-2: ethyl acrylate, CAS No. 140-88-5.
[0082] In the following examples, the amount of pre-emulsion I used was 78.54 g.
[0083] In the following examples, 1 part by weight means 9 g.
[0084] Example 1
[0085] (1) in the presence of water and a chain transfer agent (2,4-diphenyl-4-methyl-1-pentene), 100 parts by weight of monomer A', monomer B', and monomer C', initiator I (ammonium persulfate), and emulsifier I are mixed at room temperature to carry out a contact reaction (time is 20 minutes) to obtain a pre-emulsion;
[0086] (2) In the presence of initiator ⅠⅠ (ammonium persulfate) and emulsifier ⅠⅠ (sodium dodecyl sulfate), pre-emulsion I is added dropwise to a 1.5 L mixed solution containing a buffer (at a concentration of 5 mg / mL) and pre-emulsion II to carry out an emulsification reaction, and then the product obtained by the emulsification reaction is heat-treated for 2 h to obtain a heterogeneous structure gel electrolyte; pre-emulsion I and pre-emulsion II are both pre-emulsions prepared in step (1).
[0087] The specific materials and reaction conditions of this example are shown in Table 1.
[0088] Examples 2 and 3 were prepared using the same method as Example 1, except that the materials and reaction conditions were different, as shown in Table 1.
[0089] Table 1
[0090]
[0091]
[0092] Example 4
[0093] This example is carried out in a similar manner to that of Example 1, except that the amount of initiator I in this example is adjusted to 0.05 parts by weight, and the amount of emulsifier I is adjusted to 0.35 parts by weight, to obtain a heterogeneous structure gel electrolyte.
[0094] Example 5
[0095] This example is carried out in a similar manner to that of Example 1, except that the total amount of monomer A', monomer B' and monomer C' in this example is kept unchanged, and the molar ratio of monomer A', monomer B' and monomer C' is adjusted to 1:0.3:0.1 to obtain a heterogeneous structure gel electrolyte.
[0096] Example 6
[0097] This embodiment is carried out in a similar manner to that of Embodiment 1, except that in this embodiment, monomer A' is monomer A'-3, monomer B' is monomer B'-3, and monomer C' is monomer C'-2, to obtain a heterogeneous structure gel electrolyte.
[0098] Comparative Example 1
[0099] This comparative example was carried out in a similar manner to Example 1, except that the weight ratio of pre-emulsion I to pre-emulsion II in this example was adjusted to 1:0.35. As a result, it was found that monomer demulsification resulted in reaction failure, obvious oil-water stratification occurred, and the reaction product could not be applied to battery separators.
[0100] Test Case
[0101] The liquid absorption rate of the heterogeneous structure gel electrolyte obtained in the example was recorded, and the results are shown in Table 2.
[0102] At the same time, the heterogeneous structure gel electrolyte obtained in the example was coated (sprayed) on the battery separator, and then the lamination, injection and other processes were carried out to prepare a lithium-ion battery; a PVDF coated separator was prepared according to the method of Example 1 and Example 2 in Publication No. CN115000622A, and the two coatings were laminated, injected and other processes were carried out to prepare a lithium-ion battery; finally, the injection coefficient of the electrolyte during the injection of the above lithium-ion battery, the wetting effect of the positive and negative electrode sheets and the battery 1000 cycle capacity retention rate were tested. The results are shown in Table 2.
[0103] Among them, the evaluation method of the wetting effect of the positive and negative electrode plates is: judging the degree of electrode wetting by the size of the battery internal resistance.
[0104] Table 2
[0105]
[0106]
[0107] The present invention provides, by way of example, a schematic diagram of the internal structure of a heterogeneous structure gel electrolyte obtained in Example 1 and a lithium ion battery prepared therefrom, as shown in FIG. Figure 1 As shown; where M1 is the overall structure of the heterogeneous structure gel electrolyte (including lipophilic chains, lipophilic shell and hydrophilic core from outside to inside), M2 is the local structure of the heterogeneous structure gel electrolyte after swelling after absorbing the electrolyte (including the swollen shell and hydrophilic core after electrolyte infiltration from outside to inside), and M3 is the structure inside the electrode after swelling of the heterogeneous structure gel electrolyte in the lithium-ion battery (including the hydrophilic core, electrode active material and current collector from left to right);
[0108] from Figure 1 It can be seen that the hydrophobic groups on the outside of the heterostructure gel electrolyte can swell by absorbing the electrolyte in the lithium-ion battery, so that the outside of the heterostructure gel electrolyte is tightly bonded to the positive and negative electrodes, and can also well infiltrate the positive and negative electrode sheets, while the hydrophilic groups in the inner core of the heterostructure gel electrolyte hardly absorb the electrolyte.
[0109] It can be seen from the above results that the method for preparing heterogeneous structure gel electrolyte provided by the present invention not only has a high monomer reaction rate, but also has no monomer residue when coating the diaphragm, effectively avoiding monomer residue inside the battery; and compared with the prior art, this method can reduce the amount of electrolyte used and achieve cost reduction.
[0110] Moreover, when the heterogeneous structure gel electrolyte prepared by this method is applied to lithium-ion batteries, it not only has good cell wettability and can be tightly bonded to the positive and negative electrodes, but also ensures good battery cycle performance.
[0111] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A heterogeneous structure gel electrolyte, characterized in that: The gel electrolyte contains structural unit A, structural unit B and structural unit C, wherein the molar ratio of the structural unit A, the structural unit B and the structural unit C is 1:0.1-0.4:0.05-0.2; The structural unit A is shown in formula (1), the structural unit B is shown in formula (2), and the structural unit C is shown in formula (3); Wherein, in formula (1) and formula (3), R1 and R3 are each independently selected from C 1-4 Alkoxy, containing at least one oxygen atom as a ring atom C 2-6 Heterocycloalkoxy, phenyl, C 1-4 Alkanoyl, nitro, methylsulfonyl, C 1-4 The sulfonic acid group and C 1-4 One of the alkyl groups; In formula (2), R2 is selected from H, -OH, -Li, C 1-4 Alkoxy, containing at least one oxygen atom as a ring atom C 2-6 Heterocycloalkoxy, phenyl and C 1-4 One of the alkyl groups.
2. The gel electrolyte according to claim 1, wherein In formula (1) and formula (3), R1 and R3 are each independently selected from methoxy, C 2-6 Epoxy, phenyl, formyl, acetyl, nitro, methylsulfonyl, C 1-4 One of a sulfonic acid group, a methyl group and an n-butyl group; In formula (2), R2 is selected from H, -OH, -Li, methoxy, C 2-6 The epoxy group and C 1-4 One of the alkyl groups.
3. A method for preparing a heterogeneous structure gel electrolyte, characterized in that: The method includes: (1) in the presence of water and a chain transfer agent, monomer A', monomer B', monomer C', initiator I and emulsifier I are mixed to carry out a contact reaction to obtain a pre-emulsion; (2) in the presence of initiator ⅠⅠ and emulsifier ⅠⅠ, adding pre-emulsion I to a mixed solution containing a buffer and pre-emulsion II to perform an emulsification reaction to obtain the heterogeneous structure gel electrolyte; the pre-emulsion I and the pre-emulsion II are both the pre-emulsions prepared in step (1), and the weight ratio of the pre-emulsion I to the pre-emulsion II is 1:0.05-0.25; Wherein, in step (1), the molar ratio of the monomer A', the monomer B' and the monomer C' is 1:0.1-0.4:0.05-0.2; The monomer A' is selected from at least one of the monomers represented by formula (I), the monomer B' is selected from at least one of the monomers represented by formula (II), and the monomer C' is selected from at least one of the monomers represented by formula (III); The monomer A', the monomer B', and the monomer C' respectively make the gel electrolyte contain a structural unit A, a structural unit B, and a structural unit C, wherein the structural unit A is as shown in formula (1), the structural unit B is as shown in formula (2), and the structural unit C is as shown in formula (3). The definitions of R1, R2 and R3 are the same as those of R1, R2 and R3 in claim 1 or 2.
4. The method according to claim 3, wherein: In step (1), relative to 100 parts by weight of the monomer combination, the amount of the initiator I is 0.1-0.3 parts by weight, and the amount of the emulsifier I is 0.5-0.8 parts by weight; the monomer combination is the total weight of the monomer A', the monomer B' and the monomer C'.
5. The method according to claim 4, wherein: The weight ratio of the initiator I to the initiator Ⅰ is 0.2-0.4:1; And / or, the weight ratio of the emulsifier I to the emulsifier Ⅱ is 0.4-0.6:
1.
6. The method according to any one of claims 3 to 5, wherein: In step (1), the amount of the chain transfer agent is 0.1-1 parts by weight relative to 100 parts by weight of the monomer combination; The monomer combination is the total weight of the monomer A', the monomer B' and the monomer C'; And / or, the contact reaction conditions include: a rotation speed of 1200-1400 rpm and a time of 10-20 min.
7. The method according to any one of claims 3 to 6, wherein: In step (2), the pre-emulsion I is added at a flow rate of 8-9 mL / min relative to 1 L of the mixed solution; and / or, in the mixed solution, the concentration of the buffer is 4-6 mg / mL; And / or, step (2) further comprises: subjecting the product obtained by the emulsification reaction to a heat preservation treatment for 1-3 hours; And / or, the conditions of the emulsification reaction include: a rotation speed of 1000-1300 rpm, a time of 200-300 min, and a temperature of 70-90°C.
8. The method according to any one of claims 3 to 7, wherein: The initiator I and the initiator II are each independently selected from at least one of azobisisobutyronitrile, dibenzoyl peroxide, ammonium persulfate, sodium persulfate and potassium persulfate; And / or, the emulsifier I and the emulsifier II are each independently selected from anionic emulsifiers and / or nonionic emulsifiers.
9. A heterogeneous structure gel electrolyte prepared by the method according to any one of claims 3 to 7.
10. Use of the heterogeneous structure gel electrolyte according to any one of claims 1, 2 and 9 in lithium ion batteries.
Citation Information
Patent Citations
PVDF (Polyvinylidene Fluoride) coated diaphragm and preparation method thereof
CN115000622A
In-situ cured quasi-solid electrolyte and battery and preparation method thereof
CN117747932A